Análise do efeito do número de recirculação no desempenho térmico e na queda de pressão de um evaporador inundado - Mathias, Jeferson Daniel (Universidade do Vale do Rio dos Sinos, 2017)
The importance of industrial refrigeration systems is notorious, highlighting their use in large chemical and petrochemical plants and, especially in food industry, in slaughterhouses, where the energy consumption impacts directly on quality and final value of the product. The modernization of project criteria for refrigeration equipment aiming at reducing the costs of manufacturing, maintenance, installation, energy consumption and refrigerant load in the system using new materials and decreasing the volume of evaporators and separator tanks is a current need and it is being implemented by the vast majority of equipment manufacturing companies. Therefore, it is justified the importance of evaluate the efficiency refrigeration system with Liquid Overfeed Evaporator according to the variation of refrigerant’s recirculation number. The application of the concepts of Liquid Overfeed Evaporator with recirculation through the ammonia refrigerant intends to expand the studies in industrial evaporators, given the scarcity of information in this area. The results obtained from the experimental tests of flooded evaporators with liquid recirculation make it possible to quantify the influence of the recirculation number in the capacity of the evaporator and in the pressure drop of the refrigerant flow inside the tubes compared with the values estimated through the used correlations. The evaporator presented an increment of capacity by increasing the recirculation number in the order of 9.3%, varying between 108.6 and 118.7 Kw, according to collected data. It is observed that in the study of estimated and analyzed correlations for the calculation of the coefficient of heat transfer on the air side, the correlation of Kim et al. (1999) to flat fins and tubes presented the smallest relative errors for the calculation of the global heat transfer coefficient. The pressure drop during the ammonia’s flow in the evaporator for each recirculation number showed values between 15.2 and 35.7 kPa, representing an increase of 134.8%, while the quality of the refrigerant at the output of the evaporator showed its variation, related to the number of recirculation, between 0.67 and 0.248.
Keywords: Evaporador inundado; Recirculação de líquido; Correlações de transferência de calor; Liquid overfeed evaporator; Liquid recirculation; Heat transfer correlation; ACCNPQ::Engenharias::Engenharia Mecânica